Effects of dementia preventive behaviours promotion program based on health belief model among older people at risk - Koson, Noppamas; Pekalee, Alongkorn; Therawiwat, Manirat (Disease Control Journal, 2025)
Dementia is a significant problem among Thai older adults. Behavior modification is one possible prevention approach. This quasi-experimental research with two-group pretest-posttest design aimed to study the effectiveness of a dementia preventive behaviors promotion program among at-risk older adults, by integrating the concept of Health Belief Model and social support theory. The sample consisted of 62 older adults who were at risk for dementia, was equally divided into an experimental and a comparison group. The experimental group received an 8-week dementia preventive behaviors promotion program, consisting of face-to-face and online activities. The comparison group received routine health care. Data was collected using interview questionnaires Data were analyzed using descriptive statistics and inferential statistics including Chi-square test and t-test. The results showed that after the experiment, the experimental group had significantly higher mean scores of perceived susceptibilities to dementia, perceived severity of dementia, perceived benefits of preventive behaviors, cues to action, perceived self-efficacy, and dementia preventive behaviors than before the experiment and the comparison group (p<0.05). Meanwhile, perceived barriers to performing dementia preventive behaviors were significantly lower than before the experiment and the comparison group (p<0.05). The findings highlight the effectiveness of the program in encouraging dementia preventive behaviors among older adults at risk.